Castigo para los buenos : el tercer caso del sheriff Walt Longmire - Johnson, Craig, 1961-; Porras Sánchez, María; Johnson, Craig, 1961- (Madrid : Siruela : enero de 2014., 2014)
Walt Longmire has been sheriff of Wyoming's Absaroka County for almost a quarter of a century and has meted out justice with charm and a high-powered sense of humor. But when Walt tags along with good friend Henry Standing Bear on a trip to Philadelphia, he's in for a shock. A vicious attack on his daughter Cady leaves her near death and Walt discovers that she has unwittingly become embroiled in a deadly political cover-up. With Henry, Deputy Victoria Moretti, the entire Moretti clan of Philadelphia police officers, and Dog as backup, Sheriff Longmire intends to introduce a little western justice from his saddlebag of tricks to the City of Brotherly Love, where no act of kindness goes unpunished.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: Longmire, Walt -- Fiction; Sheriffs -- Pennsylvania -- Philadelphia -- Fiction; Assault and battery -- Pennsylvania -- Philadelphia -- Fiction; Corruption investigation -- Pennsylvania -- Philadelphia -- Fiction; Drug traffic -- Investigation -- Pennsylvania -- Philadelphia -- Fiction; Philadelphia (Pa.) -- Fiction; Electronic books